2009
DOI: 10.1017/s0022149x08198832
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dirofilaria immitis in dogs from Hatay province, Turkey

Abstract: The present study was conducted to determine the prevalence of canine dirofilariosis in Hatay province, south of Turkey. A total of 269 blood samples were collected from owned dogs in this multi-centre survey between March and July 2006. Blood samples were examined by modified Knott and enzyme-linked immunosorbent assay (ELISA) techniques to detect circulating microfilariae and antigens of Dirofilaria immitis, respectively. Seventy out of 269 dogs (26.0%) were positive for D. immitis. However, 61.4% of positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 22 publications
2
17
1
1
Order By: Relevance
“…The seroprevalence was 2% in Şanlıurfa [28] and 2.4% in Diyarbakır [29] which were lower than this study (6.7%). Considering the other provinces, the seroprevalence was found to be 9.1 % in Elazıg [30] , 9.3% in Ankara [31] , 9.6% in Kayseri [32] , 17.8% in Van [33] , 26% in Hatay [34] , 34.5% in Kırıkkale [35] , 40% in Igdır [36] , 46.2% in Van [14] which were higher than the seroprevalence determined in the current study. There are limited studies on the diagnosis of this nematode in dogs by molecular techniques in Turkey.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…The seroprevalence was 2% in Şanlıurfa [28] and 2.4% in Diyarbakır [29] which were lower than this study (6.7%). Considering the other provinces, the seroprevalence was found to be 9.1 % in Elazıg [30] , 9.3% in Ankara [31] , 9.6% in Kayseri [32] , 17.8% in Van [33] , 26% in Hatay [34] , 34.5% in Kırıkkale [35] , 40% in Igdır [36] , 46.2% in Van [14] which were higher than the seroprevalence determined in the current study. There are limited studies on the diagnosis of this nematode in dogs by molecular techniques in Turkey.…”
Section: Discussioncontrasting
confidence: 64%
“…It was reported that the prevalence of D. immitis was higher in outdoor, stray and suburban dog population than the indoor, owned and urban dogs [9,33,34] . Parallel to these reports, the dog population was consisting of stray dogs which were living in shelters in the present study.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…S1 in the supplemental material) (108,123,126,149,312,319,332,349,398,409,410,455,459). Cases of dirofilariasis were first reported in southern Switzerland in 1995 (109).…”
Section: Canine Dirofilariasismentioning
confidence: 99%